VAN HIELE-BASED LEARNING TO ACCELERATE PUPILS' UNDERSTANDING OF QUADRILATERAL - Yanti, Aning Wida; Jaelani, Abdulloh; A’ini, Qurrotul (IAIN Ambon, 2025)
According to the National Council of Teachers of Mathematics (NTCM), students must own geometry capabilities. However, the ability of students to understand geometry is still too low, which causes understanding concepts and skills. Students geometry ability in breakdown problems are still very weak, and geometry is taught less to students with abilities. According to Van Hiele, learning geometry has three main elements: time, materials, and teaching methods. This study aims to describe the development of learning devices based on Van Hiele's theory that can accelerate students' understanding of geometry material. This research is a development research. The learning tools developed, lesson plans, and student books were created using the ADDIE model. Subject in study this is student class VII of UPT SMP Negeri 11 Gresik. Data collection techniques use notes field, questionnaire, and test understanding geometry. Quality results development device learning must fulfill three criteria that are validity, practicality, and effectiveness. Based on the results of data analysis, it can be concluded that: 1. valid (average total validity of RPP is 4.17 and average total validity of book student by 4.29); 2. practical (average value A ( can used without revision ) for aspect theory, and average percentage mark response student, namely 90.6% (very positive ) for aspect practice ; 3. effective (percentage completeness all over student by 92.59%). The developed Van Hielel theory-based learning device can accelerate students' understanding of geometry material and meet the valid, practical, and effective criteria